An interpretative phenomenological analysis of the experiences of HIV-positive lay counsellors working in the voluntary counselling and testing settings,An interpretative phenomenological analysis of the experiences of HIV-positive lay counsellors working in the VCT settings - Teng, James Wei Jie (Rhodes University, Faculty of Humanities, Department of Psychology, 2011)
The purpose of this study was to present and understand the experiences of HIV-positive lay counsellors working in Voluntary Counselling and Testing (VCT) settings. Specifically exploring and understanding the utilisation of personal experiences within counselling encounters, the practice of peer counselling within VCT, and the challenges experienced by HIV-positive lay counsellors within VCT settings. This study, employing a qualitative interpretative phenomenological methodology required a small sample of practicing HIV-positive lay counsellors, who were selected and interviewed on their experiences utilising semi-structured interviewing. Data was analysed for meaning units, which were interpreted inductively and hermeneutically, and categorised into super-ordinate themes. Three superordinate themes within the participants' experiences of providing VCT services were determined, namely: 'diagnosis and disclosure experiences', 'peer counselling', and 'challenges'. This research found that the experiences of providing peer counselling depended upon identification with their client's negative appraisal of their diagnosis experiences. Whether through empathic connections generated through the shared experience of discovering a seropositive status, or through countertransferential reactions induced through their client's yearning for care and support. This required the counsellor to selfdisclose within counselling encounters in order to provide personal experiences of living with HIV/AIDS. Successful implementation of peer counselling provided recently diagnosed individuals with knowledge surrounding HIV/AIDS, coping skills to manage the daily physiological and psychological challenges, facilitation and adherence to treatment, social assistance, ongoing relationships, inspiring hope, and the creation of positive appraisals. However the informal utilisation of task-shifting within lay healthcare cadres, and the lack of governmental recognition for the emotional labour provided within VCT indicated that HIVpositive lay counsellors require ongoing training, support and remuneration to limit potential occupational stress, resignation, and burnout.
Keywords: HIV-positive persons; Peer counseling; Health counseling; Health counselors -- Mental health; Hiv-positive persons -- Counseling of; HIV-positive persons -- Mental health; HIV infections -- Psychological aspects; Lay analysis (Psychoanalysis)